2018
DOI: 10.1002/ange.201805696
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Gold Nanoparticles with Chelating Ligands for Highly Efficient Electrocatalytic CO2 Reduction

Abstract: Capped chelating organic molecules are presented as a design principle for tuning heterogeneous nanoparticles for electrochemical catalysis. Gold nanoparticles (AuNPs) functionalized with a chelating tetradentate porphyrin ligand show a 110‐fold enhancement compared to the oleylamine‐coated AuNP in current density for electrochemical reduction of CO2 to CO in water at an overpotential of 340 mV with Faradaic efficiencies (FEs) of 93 %. These catalysts also show excellent stability without deactivation (<5 % pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…In order to overcome this limitation, the surfactant molecules bound to Au NPs were replaced by chelating porphyrin-like tetradentate ligands with S-terminal anchoring groups. 422 The latter act as hollow scaffolds on Au NPs, interacting with the metal catalyst but without hindering the accessibility of the catalytic sites. This structural modification led to a 110-fold current enhancement in comparison with the parent oleylaminecoated Au NPs, efficiently producing CO (FE up to 93%) at an overpotential of 340 mV (Fig.…”
Section: Surface Functionalization With Organic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome this limitation, the surfactant molecules bound to Au NPs were replaced by chelating porphyrin-like tetradentate ligands with S-terminal anchoring groups. 422 The latter act as hollow scaffolds on Au NPs, interacting with the metal catalyst but without hindering the accessibility of the catalytic sites. This structural modification led to a 110-fold current enhancement in comparison with the parent oleylaminecoated Au NPs, efficiently producing CO (FE up to 93%) at an overpotential of 340 mV (Fig.…”
Section: Surface Functionalization With Organic Moleculesmentioning
confidence: 99%
“…The electronic effect due to Au-S interactions was estimated to be negligible. 422 In an earlier study, the same authors used tetrapodal S-terminal porphyrin platforms to functionalize polycrystalline Cu electrodes for electrochemical CO reduction (CORR). 423 Based on DFT calculations, the different selectivity toward oxygenates production experimentally observed for various cage sizes was tentatively ascribed to a different stabilization of a key ketene intermediate via H-bonding interactions with the porphyrin cap.…”
Section: Surface Functionalization With Organic Moleculesmentioning
confidence: 99%
“…46% after 2 hours. Numerous studies have shown the different performance of Au nanoparticles [27][28][29][30] compared to Au plate electrodes highlighting the importance of the structure and geometry of the electrode surface. The performance of CO2 reduction can be improved by the use of different Au nanoparticles in terms of size, loading and/or by the use of oxide-derived Au electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the intrinsic properties of each material, the selectivity of products from the CO 2 RR mainly depends on the initial catalyst materials. In this context, noble metals such as Au, Ag, and Pd have been the most rational choice for electrocatalysts in CO production. These noble metals have been extensively studied as representative model catalysts for CO production, to develop new strategies for high performance and to understand fundamental reaction mechanisms.…”
Section: Noble Metal Based Electrocatalystsmentioning
confidence: 99%